Perancangan Sistem Notifikasi Tamu Menggunakan Kombinasi Sensor PIR dan Ultrasonik - Dewa Putu Adrian Paramarta; I Made Widhi Wirawan (Jurnal Nasional Teknologi Informasi dan Aplikasinya, 2026)
Modern lifestyles often cause homeowners to be unaware of a guest's presence due to distracting activities like working from home, gaming, or using social media. Conventional doorbells fall short in these situations, highlighting the need for a more effective, technology-based solution. This research focuses on designing and building an innovative guest notification system based on the Internet of Things (IoT) using an ESP32 microcontroller. To enhance accuracy and reduce false positives, the system integrates a dual-sensor verification mechanism. A Passive Infrared (PIR) sensor acts as the initial trigger to detect motion, which is then verified by an HC-SR04 ultrasonic sensor to confirm the object's presence within a relevant distance from the door. A notification is sent via the Telegram application only when both conditions are met. This approach effectively filters out irrelevant movements and significantly improves reliability compared to single-sensor systems. The final prototype demonstrates an accurate, affordable, and practical solution to ensure homeowners never miss a visitor.